2021
DOI: 10.3390/antibiotics10050537
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Multidrug Efflux Pump and Alterations in Cell Surface Structure in the Synergistic Antifungal Activity of Nagilactone E and Anethole against Budding Yeast Saccharomyces cerevisiae

Abstract: Nagilactone E, an antifungal agent derived from the root bark of Podocarpus nagi, inhibits 1,3-β glucan synthesis; however, its inhibitory activity is weak. Anethole, the principal component of anise oil, enhances the antifungal activity of nagilactone E. We aimed to determine the combinatorial effect and underlying mechanisms of action of nagilactone E and anethole against the budding yeast Saccharomyces cerevisiae. Analyses using gene-deficient strains showed that the multidrug efflux pump PDR5 is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The treatment with AN+IT association showed similar efficacy to treatment with IT, but at lower doses (62.5 + 12.5 mg/kg). Fujita et al (2017) and Ueda et al (2021) reported a synergism of AN+dodecanol association and AN+naglinactone E, respectively, changing the expression of efflux pumps in yeast, and potentiating antifungals effects. As it was already mentioned above, the Grocott staining technique showed fungus presence in the joint of an infected animal, and with the histological analysis using the HE staining technique, it was observed that this fungus causes an inflammatory response with intense cell recruitment and change in synovial membrane and cartilage degradation, as demonstrated by Loth et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with AN+IT association showed similar efficacy to treatment with IT, but at lower doses (62.5 + 12.5 mg/kg). Fujita et al (2017) and Ueda et al (2021) reported a synergism of AN+dodecanol association and AN+naglinactone E, respectively, changing the expression of efflux pumps in yeast, and potentiating antifungals effects. As it was already mentioned above, the Grocott staining technique showed fungus presence in the joint of an infected animal, and with the histological analysis using the HE staining technique, it was observed that this fungus causes an inflammatory response with intense cell recruitment and change in synovial membrane and cartilage degradation, as demonstrated by Loth et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane ABC transporters, such as Pdr5, Snq2, and Yor1, export a variety of functionally and structurally unrelated compounds from cells [13,16,17]. PDR5 encodes a major efflux pump of structurally and functionally unrelated drugs and xenobiotics, such as fluconazole and cycloheximide [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the different types of discovered antifungal drugs have enabled progress in the management of fungal infections, serious problems regarding side effects, limited options of antifungals and mainly the development of drug resistance [ 30 , 31 , 32 , 33 ], highlight the urgent need of exploring new therapeutic approaches that overpass the unmet clinical needs [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%